Clinical presentation of CIED infection following initial implant versus reoperation for generator change or lead addition. Issue 1 (30th March 2018) - Harper, Mariko W; Uslan, Daniel Z; Greenspon, Arnold J; Baddour, Larry M; Carrillo, Roger G; Danik, Stephan B; Tolosana, Jose M; Le, Katherine; Miro, Jose M; Naber, Christoph K; Peacock, James; Sohail, Muhammad Rizwan; et al.
Abstract : Objective: To explore differences in clinical manifestations and outcomes in those patients who develop infection after undergoing initial implantation versus reoperation. Methods: We compared cases of cardiac implantable electronic device (CIED) infection based on initial implantation versus reoperation from 11 centres. Results: There were 432 patients with CIED infection, 178 occurring after initial device placement and 254 after repeat reoperation. No differences were seen in age, sex or device type. Those with infection after initial implant had a higher Charlson Comorbidity Score (median 3 (IQR 2–6) vs 2 (IQR 1–4), p<0.001), shorter time since last procedure (median 8.9 months (IQR 0.9–33.3) vs 19.5 months (IQR 1.1–62.9), p<0.0001) and fewer leads (2.0±0.6vs 2.5±0.9, p<0.001). Pocket infections were more likely to occur after a reoperation (70.1%vs48.9%, p<0.001) and coagulase negative staphylococci (CoNS) was the most frequently isolated organism in this group (p=0.029). In contrast, initial implant infections were more likely to present with higher white cell count (10.5±5.1 g/dL vs 9.5±5.4 g/dL, p=0.025), metastatic foci of infection (16.9%vs8.7%, p=0.016) and sepsis (30.9%vs19.3%, p=0.006). There were no differences in in-hospital (7.9%vs5.2%, p=0.31) or 6-month mortality (21.9%vs14.0%, p=0.056). Conclusions: CIED infections after initial device implant occur earlier, more aggressively, and often due to Staphylococcus aureus . In contrast, CIED infections after reoperation occur later, are due to CoNS, and have more indolent manifestations with primary localisation to the pocket.